miRNA mediated downregulation of cyclase-associated protein 1 (CAP1) is required for myoblast fusion - Singh, Anurag Kumar; Rai, Amrita; Weber, Anja; Posern, Guido (Frontiers in Cell and Developmental Biology, 2022)
Myoblast fusion is essential for the formation, growth, and regeneration of skeletal muscle, but the molecular mechanisms that govern fusion and myofiber formation remain poorly understood. Past studies have shown an important role of the actin cytoskeleton and actin regulators in myoblast fusion. The Cyclase-Associated Proteins (CAP) 1 and 2 recently emerged as critical regulators of actin treadmilling in higher eukaryotes including mammals. Whilst the role of CAP2 in skeletal muscle development and function is well characterized, involvement of CAP1 in this process remains elusive. Here we report that CAP1, plays a critical role in cytoskeletal remodeling during myoblast fusion and formation of myotubes. Cap1 mRNA and protein are expressed in both murine C2C12 and human LHCN-M2 myoblasts, but their abundance decreases during myogenic differentiation. Perturbing the temporally controlled expression of CAP1 by overexpression or CRISPR-Cas9 mediated knockout impaired actin rearrangement, myoblast alignment, expression of profusion molecules, differentiation into multinucleated myotubes, and myosin heavy chain expression. Endogenous Cap1 expression is post-transcriptionally downregulated during differentiation by canonical myomiRs miR-1, miR-133, and miR-206, which have conserved binding sites at the 3′ UTR of the Cap1 mRNA. Deletion of the endogenous 3′ UTR by CRISPR-Cas9 in C2C12 cells phenocopies overexpression of CAP1 by inhibiting myotube formation. Our findings implicates Cap1 and its myomiR-mediated downregulation in the myoblast fusion process and the generation of skeletal muscle.